2015
DOI: 10.1016/j.stemcr.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Reveals Disruption of Striatal Neuronal Development and Therapeutic Targets in Human Huntington’s Disease Neural Stem Cells

Abstract: SummaryWe utilized induced pluripotent stem cells (iPSCs) derived from Huntington’s disease (HD) patients as a human model of HD and determined that the disease phenotypes only manifest in the differentiated neural stem cell (NSC) stage, not in iPSCs. To understand the molecular basis for the CAG repeat expansion-dependent disease phenotypes in NSCs, we performed transcriptomic analysis of HD iPSCs and HD NSCs compared to isogenic controls. Differential gene expression and pathway analysis pointed to transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
134
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(156 citation statements)
references
References 53 publications
18
134
0
2
Order By: Relevance
“…These findings collectively indicate that undifferentiated cells harboring the LIN28A mutation are already poised to develop the disorder. These data are consistent with reports demonstrating disease phenotypes and perturbed expression of disease‐associated genes in iPSCs and NSCs derived from Huntington's disease patients (An et al , ; Camnasio et al , ; Ring et al , ). All of these findings suggest that the first steps in disease pathogenesis of adult‐onset neurodegenerative diseases may occur during embryonic development (Humbert, ; Brennand, ).…”
Section: Resultssupporting
confidence: 92%
“…These findings collectively indicate that undifferentiated cells harboring the LIN28A mutation are already poised to develop the disorder. These data are consistent with reports demonstrating disease phenotypes and perturbed expression of disease‐associated genes in iPSCs and NSCs derived from Huntington's disease patients (An et al , ; Camnasio et al , ; Ring et al , ). All of these findings suggest that the first steps in disease pathogenesis of adult‐onset neurodegenerative diseases may occur during embryonic development (Humbert, ; Brennand, ).…”
Section: Resultssupporting
confidence: 92%
“…TGFβ signaling is implicated as a ‘switching factor’ whose levels and temporal activity require tight regulation during development to determine neuronal cell fate 22 . This signaling network was disrupted in neural stem cells from HD patient iPSCs 23 . Highlighted in this network were genes overlapping the IPA-predicted regulators and genes that are major hubs with direct connections to other genes in the larger network, suggesting an association with HD.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that TGF- β signaling pathway is altered in HD NSC with 72 CAGs that leads to higher expression of TGF- β . Furthermore, TGF- β 1 plays neuroprotective role in the NSC models and together with netrin-1 can reduce caspase 3/7 activity [94]. …”
Section: Ipscs Providing New Tools For Developing Treatments For Cmentioning
confidence: 99%